Evaluation of the myocardial deformation in the diagnosis of rejection after heart transplantation - Rodrigo Cordovil Pinto Lobo da Costa; Ana Clara Tude Rodrigues; Marcelo Luiz Campos Vieira; Claudio Henrique Fischer; Claudia Gianini Monaco; Edgar Bezerra Lira Filho; Fernando Bacal; Adriano Caixeta; Samira Saady Morhy (Frontiers in Cardiovascular Medicine, 2022)
IntroductionHeart transplantation represents main therapy for end-stage heart failure. However, survival after transplantation is limited by development of graft rejection. Endomyocardial biopsy, an invasive and expensive procedure, is gold standard technique for diagnosis of rejection. Most of biopsy complications are observed using echocardiography. Novel echocardiographic techniques, such as myocardial strain and three-dimensional reconstruction, can be useful in heart transplant patients.PurposeTo evaluate ventricular strain in heart transplant patients and association with rejection, cellular or humoral, as well as two- and three-dimensional echocardiographic parameters.MethodsCohort of patients from heart transplant program taken to echocardiography after endomyocardial biopsy, from December 2017 to January 2020. Ventricular strain and three-dimensional left ventricle parameters were studied. Rejection results were retrieved from medical record. Qualitative variables were expressed by absolute frequency and percentages, while continuous variables by means and standard deviations. Association between rejection and variables of interest was measured by odds ratio and confidence interval of 95%, with p-value < 0.05.Results123 post-endomyocardial biopsy echocardiographic exams were performed in 54 patients. Eighteen exams were excluded, lasting 105 exams to be evaluated for conventional and advanced echocardiographic parameters. Male patients were 60.4%. Prevalence of cellular rejection was 8.6%, humoral rejection 12.4%, and rejection of any type 20%. There was no association between right ventricular strain and rejection, whether cellular (p = 0.118 and p = 0.227 for septum and free wall, respectively), humoral (p = 0.845 and p = 0.283, respectively), or of any type (0.504 and 0.446). There was no correlation between rejection and left ventricle global longitudinal strain, three-dimensional ejection fraction or desynchrony index. Conventional parameters associated to rejection were left ventricle posterior wall thickness [OR 1.660 (1.163; 2.370), p = 0.005] and left ventricle mass index [OR 1.027 (1.011; 1.139), p = 0.001]. Left ventricle posterior wall thickness remained significant after analysis of cellular and humoral rejection separately [OR 1.825 (1.097; 3.036), p = 0.021 and OR 1.650 (1.028; 2.648), p = 0.038, respectively].ConclusionsThere was no association between ventricular strain, three-dimensional left ventricular ejection fraction and the desynchrony index and rejection, cellular or humoral. Evidence of association of graft rejection with left ventricle posterior wall thickness and left ventricle mass index was observed.